Pain Management in Patients with Multiple Sclerosis - T Jock Murray (Pain Research and Management)
Although the idea that pain is not a symptom of multiple sclerosis (MS) continues, many studies have confirmed that over half of MS patients complain of pain. In some patients, it may be in part a result of the exacerbation of the disease. In other patients, it is an acute pain problem such as trigeminal neuralgia, bladder spasms, acute dysesthesia, Lhermitte's phenomenon or painful tonic spasms. In even more cases, it is chronic pain that can take the form of dysesthesia, or repeated muscle spasms and aching. Although MS can cause pain, increasing disability can also produce other complications that are painful such as pressure palsies, decubiti, the effects of poorly fitting wheelchairs, or the musculoskeletal pain that results from the effort to maintain head position and posture with weakened muscles. All of the problem that MS patients experience do not necessarily result from their MS. MS patients can develop all of the medical conditions and pain situations that afflict the rest of the population, and these are usually manageable when the correct diagnosis is made and the approach is focused. Overall, most of the conditions causing pain in MS can be prevented, eliminated or improved, and the remaining patients with chronic pain are managed with strategies that are useful in approaching chronic pain in other situations.